2011
DOI: 10.1111/j.1468-5973.2011.00657.x
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Experience as a (Critical) Factor in Crisis Communication Planning

Abstract: A key issue in crisis communication is the way people process crisis-relevant information to minimize danger.This paper discusses the impact of previously experienced crises on the public's interpretation of warning messages. People may not have direct experience of a crisis, but they still have acquired mediated experiences of a variety of crises. The present study introduces the term cultural experience of crisis to label the synthesis of mediated crisis experiences, media and fictional narratives, collectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Our focus groups revealed that there are also situations where people, having heard about a possible threat, do not consider seeking additional information from outside sources. They ‘leave’ the imagined space where the information circulates via either the mass media or informal networks and may just act (e.g., escape) or ignore a warning (e.g., go out to look at the storm), relying on their own direct and culturally transmitted experience (see Harro‐Loit et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our focus groups revealed that there are also situations where people, having heard about a possible threat, do not consider seeking additional information from outside sources. They ‘leave’ the imagined space where the information circulates via either the mass media or informal networks and may just act (e.g., escape) or ignore a warning (e.g., go out to look at the storm), relying on their own direct and culturally transmitted experience (see Harro‐Loit et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Because of the qualitative nature of the data, this study aims to make no generalizations about the spread of the discovered response strategies in a particular society. The cross‐case analysis informed that a person may internalize different response patterns in different situations for a number of reasons, such as the social stigma connected with certain risks in particular society (Harro‐Loit, Vihalemm, & Ugur, ). Thus, the quantitative mapping of response strategies should be context specific.…”
Section: Methodsmentioning
confidence: 99%
“…Aside from cultural context, cultural experiences play a role. Harro Loit, Vihalemm, and Ugur () note how despite group memberships, individual experiences differ. In addition, Wan () notes the role of resonance for crisis response strategies.…”
Section: Crisis Response Strategies Revisitedmentioning
confidence: 99%
“…I nformation seeking before and during disasters is a complex multi-process behaviour (Anthony, Cowden-Hodgson, Dan O'Hair, Heath & Eosco, 2014;Choo 2009;Harro-Loit, Vihalemm & Ugur, 2012;Mileti & Beck, 1975;Parker, Priest & Tapsell, 2009;Sorensen, 2000;Wester, 2009). Following receipt of a warning message, recipients want more information and work to confirm the warning (Mileti & Sorensen, 1990), often by seeking social confirmation of the message (Huang, Starbird, Orand, Stanek & Pedersen, 2015;Quarantelli 1982) or by evaluating environmental cues of the storm or hazard (Lindell, Lu & Prater, 2005).…”
Section: Introductionmentioning
confidence: 99%